THE SOCIAL PROTECTION RIGHTS FROM PRE & POST-PLACEMENT WOMEN MIGRANT WORKERS PERPECTIVE - Istianah Istianah; Johanna Debora Imelda (Politeknik Kesejahteraan Sosial Bandung, 2020)
Migrant workers’ social protection rights include the rights to access healthcare services, medication, social services, and social security. Social security branch applicable for migrant workers are for instance social insurance, universal coverage, provident funds, individual private accounts, employer-liability schemes, and social assistance. Indramayu as the highest migrant workers sender district until April 2019, is also a district with the highest complaint in 2018 and several cases related to social protection. With 148 total cases reported from Indramayu leads to the question of whether women migrant workers from Indramayu understand social protection and its function to protect them and prevent them from poverty. Therefore, this study aims at providing an overview pertaining social protection rights to migrant workers based on the perspective of pre and post-placement women migrant workers from Indramayu District with Hongkong, China as the host country. This is historical-comparative qualitative study with purposive sampling to 10 pre and post-placement women migrant workers. The findings demonstrated that social security obtained by the women migrant workers from Indramayu is social insurance from the home country and healthcare insurance for workers from the host country. At the host country, women migrant workers are protected with healthcare insurance from the employer while at the home country, women migrant workers are protected with social insurance for migrant workers known as BPJS Ketenagakerjaan TKI, whose occupational injury and death insurance schemes are mandatory for all migrant workers. For women migrant workers, healthcare insurance in the host country is much more crucial than BPJS for TKI. It is expected from the findings of this study could be considered by the stakeholders of migrant workers to enhance and to extend the coverage of protection for migrant workers especially woman migrant workers.